Poikilodermatous Plaque-like Hemangioma: Case Presentation and Literature Review - Pablo Díaz-Calvillo; Francisco Vílchez-Márquez; Francisco Manuel Ramos-Pleguezuelos; Salvador Arias-Santiago (MDPI AG, 2024)
Poikilodermatous plaque-like hemangioma (PPH) is a recently described clinical and pathological entity, with only 18 cases reported in the literature. Although uncommon, this benign condition presents consistent clinical and histological findings. We present a new case of PPH in an 81-year-old male and review the existing literature. The persistence over time and the need to distinguish PPH from more significant lesions underscore the importance of its clinical and pathological recognition.